Pulmonary artery aneurysm in a newborn: a case report (SigMe, 2025)
Pulmonary artery aneurysm is a rare entity in newborns, with variable etiologies and an unspecific clinical course. We present the case of a full-term newborn admitted at 48 hours of age with dyspnea and cyanosis. Echocardiogram revealed pulmonary artery dilation, which was confirmed by CT angiography. The patient was referred to a higher-level center for surgical evaluation. This case underscores the importance of early diagnosis and an individualized approach to rare congenital anomalies.
Keywords: Pulmonary artery aneurysm; Newborn; Neonatal cardiology